2016
DOI: 10.1016/j.talanta.2016.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Performance review of a fast HPLC-UV method for the quantification of chlorogenic acids in green coffee bean extracts

Abstract: The aim of this study was to test the performance of a HPLC method, designated for rapid quantification of chlorogenic acids (CGA) in green coffee extract (GCE). The precision statistics associated with the method were assessed using three independent laboratories with five samples analyzed in triplicate. Seven main CGA isomers (3-CQA, 5-CQA, 4-CQA, 5-FQA, 3,4-diCQA, 3,5-diCQA and 4,5-diCQA) were quantified. The concentration of total CGA in the samples varied from 32.24% to 52.65% w/w. The repeatability and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 23 publications
4
53
0
1
Order By: Relevance
“…It should be also remembered that even when using the same analytical technique, different equipment and different settings can be selected. A great example of how the change of apparatus can change the result of the CQAs analysis of the same sample carried out even by the same methodology in different laboratories is the work of Craig et al (2016). The fact that CQAs constitute a large family of compounds with various properties present in natural samples on different concentration levels, makes their analysis additionally more difficult.…”
Section: Chlorogenic Acids Analysismentioning
confidence: 99%
“…It should be also remembered that even when using the same analytical technique, different equipment and different settings can be selected. A great example of how the change of apparatus can change the result of the CQAs analysis of the same sample carried out even by the same methodology in different laboratories is the work of Craig et al (2016). The fact that CQAs constitute a large family of compounds with various properties present in natural samples on different concentration levels, makes their analysis additionally more difficult.…”
Section: Chlorogenic Acids Analysismentioning
confidence: 99%
“…For example, fingerprinting strategies using nuclear magnetic resonance (NMR) [14,22] or infrared (IR) [21,23] spectroscopy, as well as direct infusion-mass spectrometry [24], have been described to investigate adulterant contents in coffee samples. For the separation and quantification of bioactive substances in coffees to address adulteration practices, liquid chromatography (LC) with ultraviolet (UV) [13,[25][26][27][28], fluorescence [29], and amperometric [17] detection, gas chromatography (GC) [11], and capillary electrophoresis [16,20,30] are widely used, in most cases in combination with mass spectrometry. For example, Daniel et al [16] reported the monosaccharide profiling determination by capillary electrophoresis-mass spectrometry (CE-MS) to detect the adulteration of coffee samples with soybean and corn.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lower quality of robusta coffee beans, it is popular as instant coffee in the beverage industry [3]. Green coffee beans contain polyphenol compounds, such as chlorogenic acid and its related compounds (caffeic acid, ferulic acid, and coumaric acid) which are used to inhibit the oxidative stress [4]. Phenolic compounds have attracted interest because of their antioxidant potential and anti-inflammatory activity [5,6].…”
Section: Introductionmentioning
confidence: 99%